STAKEHOLDER'S PERCEPTION OF TRANSPARENCY IN VILLAGE FUND MANAGEMENT IN TOTO SELATAN VILLAGE, KABILA DISTRICT, BONE BOLANGO REGENCY - Sartin Katili; Rizal; Aryati Hamzah (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to determine stakeholder perceptions of the Transparency of Village Fund Management in South Toto Village, Kabila District, Bone Bolango Regency, with reference to the Minister of Home Affairs Regulation No. 20 of 2018 concerning Village Financial Management. This research method uses descriptive research with a qualitative approach. Data collection techniques used in this study was through observation, in-depth interviews and documentation. The results of this study indicate that stakeholder access in the budget accountability report has been carried out in the form of a Transparency Board / Billboard, so that all activities and their budgets can be seen by stakeholders. The weakness is that if there is a change in activities and budgets, then stakeholders do not have access to these changes. Independent audit involvement in budget transparency has been carried out. The audit was carried out by the Regency Inspectorate regarding finances and accountability reports for all activities that had been carried out. The weakness is that most stakeholders do not know the results of the examination or audit. Stakeholder involvement in budget decision making has been carried out, every planning stage always involves the BPD, LPM and the community. The weakness is that community involvement is only in the form of providing ideas and proposals related to the needs in each hamlet, but the stages of determining them are no longer involved.